Research protocol for an epidemiological study on estimating disease burden of pediatric HIV in Belgaum district, India - Anju Sinha; Anita Nath; Rajeev Sethumadhavan; Shajy Isac; Reynold Washington (BMC, 2016)
Abstract Background Pediatric HIV is poised to become a major public health problem in India with the rising trend of HIV infection in pregnant women (Department of AIDS Control, Ministry of Health and Family Welfare, http://www.naco.gov.in). There is lack of information on the epidemiology of pediatric HIV infection in India. Existing surveillance systems tend to underestimate the Pediatric burden. The overall aim of the present study is to estimate the disease burden of pediatric HIV among children in Belgaum district in the state of Karnataka in Southern India. An innovative multipronged epidemiological approach to comb the district is proposed. Methods The primary objectives of the study would be attained under three strategies. A prospective cohort design for objective (i) to determine the incidence rate of HIV by early case detection in infants and toddlers (0-18 months) born to HIV infected pregnant women; and cross sectional design for objectives (ii) to determine the prevalence of HIV infection in children (0-14 years) of HIV infected parents and (iii) to determine the prevalence of HIV in sick children (0-14 years) presenting with suspected signs and symptoms using age specific criteria for screening. Burden of pediatric HIV will be calculated as a product of cases detected in each strategy multiplied by a net inflation factor for each strategy. Study participants (i) (ii) (iii): HIV infected pregnant women and their live born children (ii) Any HIV-infected man/woman, of age 18-49 years, having a biological child of age 0-14 years (iii) Sick children of age 0-14 years presenting with suspected signs and symptoms and satisfying age-specific criteria for screening. Setting and conduct: Belgaum district which is a Category 'A' district (with more than 1 % antenatal prevalence in the district over the last 3 years before the study). Age-appropriate testing is used to detect HIV infection. Discussion There is a need to strengthen existing pediatric HIV estimation methods in India and other developing countries. We hope that the novel methodology emanating from this study would be applicable for estimating the burden of HIV in other settings and it would be adaptable for estimating the burden of other infectious/chronic diseases. Findings from this study will give future direction to the national program for prevention and control of HIV in India and other developing countries.